4‐Methylcatechol inhibits cell growth and testosterone production in TM3 Leydig cells by reducing mitochondrial activity. (5th May 2016) - Li, C.‐J.; Jiang, Y.‐W.; Chen, S.‐X.; Li, H.‐J.; Chen, L.; Liu, Y.‐T.; Gao, S.; Zhao, Y.; Zhu, X.‐L.; Wang, H.‐T.; Wang, F.‐G.; Zheng, L.; et al.
Summary: 4‐Methylcatechol (4‐MC) is a potential neuroprotective drug because it stimulates the synthesis of brain‐derived neurotrophic factor (BDNF) and nerve growth factor (NGF) in neurons. The present study explored the effect of 4‐MC on cell growth and testosterone synthesis in the TM3 Leydig cells of mice. 4‐MC did not enhance expression of both BDNF and NGF in these cells. However, this compound significantly inhibited cell proliferation and increased the number of apoptotic cells in a dose‐dependent manner. The expression profile of Bax/Bcl‐2 gene was altered considerably, and mitochondrial activity was significantly decreased in cells. 4‐Methylcatechol also inhibited testosterone synthesis in TM3 Leydig cells. The inhibitory roles of this compound in relation to growth and testosterone synthesis in TM3 Leydig cells maybe associated with increased Bax gene expression and decreased mitochondrial activity. As a result, caspase cascade is activated.